Analysis of Mineral Water Distribution Using Apriori Algorithm Method - Yuza Reswan; Dedy Abdullah; Anisya Sonita; Laura Anggraini (Penerbit Jurnal Indonesia, 2023)
Normalization is a process used to prepare data so that it can be used to meet user needs and support subsequent processes to get better results. The image normalization application system with Resizing Image is implemented using the matlab programming language. The mechanism for making an application starts from making a GUI (Graphic User Interface) to making coding. This thesis presents a system model of image normalization using k-space transformation to get the result in the form of an image normalization display using image resizing. The creation of an image normalization system using k-space transformation was carried out using the Matlab programming language version 2021a. The results of the system functionality test show that the image normalization system using the built resizing image can be used properly.